A new species of Tocoyena (Rubiaceae, Gardenieae) from the Brazilian Atlantic Forest - Borges, Rodrigo L.; Gaem, Paulo Henrique; Roque, Nádia (Phytotaxa, 2020)
Tocoyena atlantica, a new species endemic to southern Bahia and northern Espírito Santo states, Brazil, is here described and illustrated. The species consists of trees 5−8 m tall; with petioles 2−5 cm long, and leaf blades 7.4−24.5 × 2.5−9.1 cm, elliptic, adaxially glabrous; calyces cup-shaped with triangular lobes; corolla yellow during anthesis, with tube gradually wider towards the mouth; and laterally compressed hypanthia. Based on IUCN criteria, we consider T. atlantica endangered, with three collection localities within the Atlantic Forest domain. An identification key for species of Tocoyena occurring in the Brazilian Atlantic Forest is also provided.